Diffuse seismicity in seismic hazard assessment for site evaluation of nuclear installations. (Safety reports series, 2016)
"Diffuse seismicity refers to earthquakes occurring in locations where no apparent correlation can be made with any causative faults. The possibility of such earthquakes must be taken into consideration for nuclear installation sites, even for low to moderate seismicity regions, and their potential influence has to be assessed appropriately. This publication provides guidance for addressing the seismic hazard from diffuse seismicity in a manner consistent with internationally recognized practices and with reference to relevant IAEA Safety Standards."--Publisher's description.